Berbagai Intervensi yang Dapat Mengurangi Kesepian pada Lansia - Fahrudiana, Fuadah; Kusbaryanto, Kusbaryanto (Universitas Ahmad Dahlan, 2019)
Background: The relationship between loneliness and the consequences of its harm to physical and mental health in the elderly is often reported, including an increased risk of death. Interventions that can reduce the problem of loneliness in the elderly are needed so that they are successful in the process of aging and prosperous both biologically and psychosocially. This study aims to summarizing current knowledge about several interventions that can reduce loneliness problems in the elderly. Method: This study uses the literature review method. The database used in the literature searches is the Science Direct, Pubmed, and Google Scholar. In the early phase of searching using keywords: “older people, loneliness, interventions, programs, outcomes”, it is obtained the results of 12 international journals from the period of 2017 to 2019 that matched the inclusion criteria. Results: From the 12 journals obtained, 6 are quantitative studies, 5 are literature review studies, and 1 is a qualitative study. It is revealed the results that some interventions categorized in the direct and indirect interventions are summarized and can reduce the problem of loneliness in the elderly. Conclusion: This review identified 10 out of 11 interventions (90.9%) using a community-based group approach and the other (9.1%) using new technologies approach. Although the number of studies on interventions that target loneliness in the elderly continues to increase, our reviews above do not reach solid and strong conclusions and their characteristics can be questioned.